Early changes in scores of chronic damage on transplant kidney protocol biopsies reflect donor characteristics, but not future graft function. (9th October 2013) - Caplin, Ben; Veighey, Kristin; Mahenderan, Arundathi; Manook, Miriam; Henry, Joanne; Nitsch, Dorothea; Harber, Mark; Dupont, Peter; Wheeler, David C.; Jones, Gareth; Fernando, Bimbi; Howie, Alexander J.; et al.
Abstract The amount of irreversible injury on renal allograft biopsy predicts function, but little is known about the early evolution of this damage. In a single‐center cohort, we examined the relationship between donor‐, recipient‐, and transplantation‐associated factors and change in a morphometric index of chronic damage (ICD) between protocol biopsies performed at implantation and at 2–3 months. We then investigated whether early delta ICD predicted subsequent biochemical outcomes. We found little evidence to support differences between the study group, who had undergone serial biopsies, and a contemporaneous control group, who had not. In allografts with serial biopsies (n = 162), there was an increase in ICD between implantation (median: 2%, IQR:0–8) and 2–3 months post‐transplant (median 8% IQR:4–15; p < 0.0001). Donation from younger or live donors was independently associated with smaller early post‐transplant increases in ICD. There was no evidence for a difference in delta ICD between donation after cardiac death vs. donation after brain death, nor association with length of cold ischemia. After adjustment for GFR at the time of the second biopsy, delta ICD after three months did not predict allograft function at one yr. These findings suggest that graft damage develops shortly after transplantation and reflects donor factors, but does not predict future biochemical outcomes.